Detection of a Babesia sp. genotype closely related to marsupial-associated Babesia spp. in male Haemaphysalis shimoga from Sarawak, Malaysian Borneo - Alice, Cc Lau; Yongjin, Qiu; Mohamed Abdallah, Mohamed Moustafa; Ryo, Nakao; Michito, Shimozuru; Manabu, Onuma; Nobuyoshi, Nakajima; Mariko, Sashika; Mohd Azlan, Jayasilan; Toshio, Tsubota (Japanese Society Of Veterinary Science, 2022)
In this study, Babesia screening was conducted in 55 rodents and 160 tick samples collected from primary forests and an oil palm plantation in Sarawak, Malaysian Borneo. PCR targeting the 18S ribosomal DNA revealed the presence of Babesia spp. DNA detected in two questing male Haemaphysalis shimoga ticks collected from the oil palm plantation. Sequence analysis revealed that both sequences were identical and had 98.6% identity to a Babesia macropus sequence obtained from Eastern grey kangaroos (Macropus giganteus) in Australia. Phylogenetic tree revealed clustering with marsupial-associated Babesia spp. in the Babesia sensu stricto clade. Whether or not H. shimoga is the competent vector and the importance of the Babesia sp. detected in this study warrants more investigation.